Improving Consumer Legal Protection in E-Commerce: Analysis of Shopee's Policies and Mechanisms in Combating Counterfeit Products - Permatasari, Hanny Indah; Sudiro, Amoury Adi (Al-Bayyinah, 2024)
Online marketplaces like Shopee offer unrivaled access to global products in the digital era. Online marketplaces have become the primary means of buying and selling, making it easy for consumers to obtain various products. However, this convenience also brings challenges, especially regarding legal protection for consumers. One of the problems that often arises is the sale of products that do not match the description. This study evaluates Shopee's policies and mechanisms in ensuring product authenticity and handling consumer complaints related to counterfeit goods. Using a qualitative approach with document analysis, this study explores Shopee's merchant agreements and consumer experiences. The research findings show that despite its strict policies, there are still gaps in the enforcement and complaint resolution mechanisms, which contribute to consumer distrust. There are still many cases of goods purchased by consumers that do not match the description, which is detrimental to consumers. Law Number 8 of 1999 concerning Consumer Legal Protection explicitly regulates consumer rights, such as obtaining open information from sellers. This gap requires an evaluation of the effectiveness of consumer protection policies against counterfeit product fraud cases. Recommendations provided include improving the verification process, proactive monitoring, and transparency in sanctions to strengthen consumer legal protection. This research contributes to the importance of consumer legal protection in e-commerce, offering insights for policy improvement and empowering consumers to navigate online transactions safely.